Bounds on the finite-sample risk for exponential distribution. - Rizk, Mohamed M. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we derive lower and upper bounds on the expected nearest neighbor distance for exponential distribution, and find lower and upper bounds on the risk of the nearest neighbor of exponential distribution.